Cotratamento de lixiviado de aterro sanitário e esgoto doméstico em reatores UASB – estudo da viabilidade econômica do aproveitamento energético de biogás em Sergipe - Maia, Luisa Maria Horta (2020)
In Brazil, landfills are the most common form of municipal solid waste disposal. Its liquid effluent, the landfill leachate, has a rich polluting load and must be treated prior to final disposal. Combined treatment of landfill leachate at Wastewater treatment plants (WWTP) is widely used in the United States, Europe and Japan. In Brazil, as well as in Latin America, UASB anaerobic digestion reactors are largely used in the WWTPs, one of the characteristics of which is the production of biogas that can be used for the production of electricity. The State of Sergipe has a landfill that currently sends its leachate to an effluent treatment plant in Bahia. This research aims to evaluate the economic feasibility of implementing biogas recovery systems in the WWTPs that is already equipped with UASB reactors, in the State of Sergipe, adding the landfill leachate to the sewage in comparison with the feasibility presented by Miranda (2008), who used only sanitary sewage. Characterization data were used for the leachate produced at the Sergipe landfill and the sewage received at the stations. From the literature, it was decided to evaluate the proportion of leachate addition between 0.5% and 5% to the sanitary sewage. The ProBio 1.0 software was used to estimate the biogas generation in each of the proportions and, consequently, the energy potential in each of the stations. Using energy parameter data, the monthly energy savings generated by the use of biogas were determined. In the economic analysis, the net present values of the investments were determined for a 25-year horizon, and their return times were defined by discounted PayBack. Even with the addition of leachate, the production of biogas is still not enough to meet the daily energy demands of the WWTPs, the injection of the energy produced in the concessionaire's net being the best option. The implementation of the recovery system, without considering the income generated by charging for the leachate treatment, proved to be economically viable for three of the four WWTPs. The South WWTP, the West WWTP and Rosa Elze’s WWTP, with return on investment times of 11 years and 10 months, 12 years and 11 months and 19 years and 7 months, and net present values of R$ 1.225.215, R$ 1.001.668 and R$ 208.732, respectively, for the proportion of 5% of leachate added to sanitary sewage. Considering the income generated by charging for the leachate treatment, all the WWTPs would make the use of biogas viable. The renovation only of the South WWTP would be sufficient to receive the amount of leachate produced at the Sergipe landfill in proportions of less than 5%.